Bilateral experimental neck pain reorganize axioscapular muscle coordination and pain sensitivity. (11th November 2016) - Christensen, S.W.; Hirata, R.P.; Graven‐Nielsen, T.
Abstract: Background: Neck pain is a large clinical problem where reorganized trunk and axioscapular muscle activities have been hypothesised contributing to pain persistence and pain hypersensitivity. This study investigated the effects of bilateral experimental neck pain on trunk and axioscapular muscle function and pain sensitivity. Methods: In 25 healthy volunteers, bilateral experimental neck pain was induced in the splenius capitis muscles by hypertonic saline injections. Isotonic saline was used as control. In sitting, subjects performed slow, fast and slow‐resisted unilateral arm movements before, during and after injections. Electromyography (EMG) was recorded from eight shoulder and trunk muscles bilaterally. Pressure pain thresholds (PPTs) were assessed bilaterally at the neck, head and arm. Data were normalized to the before‐measures. Results: Compared with control and post measurements, experimental neck pain caused (1) decreased EMG activity of the ipsilateral upper trapezius muscles during all but slow‐resisted down movements ( p < 0.001), and (2) increased EMG activity in the ipsilateral erector spinae muscle during slow and fast movements ( p < 0.02), and in the contralateral erector spinae muscle during all but fast up and slow‐resisted down movements ( p < 0.007). The PPTs in the painful condition increased at the head and arm compared with post measurements and the control condition ( p < 0.001). In the post‐pain condition, the neck PPT was decreased compared with the control condition ( p < 0.001). Conclusion: Acute bilateral neck pain reorganized axioscapular and trunk muscle activity together with local hyperalgesia and widespread hypoalgesia indicating that acute neck pain immediately affects trunk and axioscapular function which may affect both assessment and treatment. Significance: Bilateral clinical neck pain alters axioscapular muscle coordination but only effects of unilateral experimental neck pain has been investigated. Bilateral experimental neck pain causes task‐dependent reorganized axioscapular and trunk muscle activity in addition to widespread decrease in pressure pain sensitivity.